Smart cities, green technologies, and intelligent transport systems : 5th International Conference, SMARTGREENS 2016, and Second International Conference, VEHITS 2016, Rome, Italy, April 23-25, 2016, Revised selected papers /: 5th International Conference, SMARTGREENS 2016, and Second International Conference, VEHITS 2016, Rome, Italy, April 23-25, 2016, Revised selected papers. (2017) - Unknown
No abstract available